Imidazopyridyl compounds as aldosterone synthase inhibitors. Issue 2 (15th January 2017) - Whitehead, Brent R.; Lo, Michael M.-C.; Ali, Amjad; Park, Min K.; Hoyt, Scott B.; Xiong, Yusheng; Cai, Jiaqiang; Carswell, Emma; Cooke, Andrew; MacLean, John; Ratcliffe, Paul; Robinson, John; et al.
Graphical abstract: Abstract: The inhibition of aldosterone synthase (CYP11B2) may be an effective treatment of hypertension and heart failure, among other ailments. Previously reported benzimidazole CYP11B2 inhibitors led the way for bioisosteric imidazopyridines that are both potent and selective over CYP11B1.